Investigating The Use of Online Transportation for Generation Z In Jakarta: Are Users Satisfied with Switching Payments from Cash to Cashless? - Michael Christian; Ongky Alex Sander; Eko Retno Indriyarti; Suryo Wibowo; Henilia Yulita; Sunarno Sunarno (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
Individual views can be shaped by price promotions, particularly when it comes to a service or service. This also applies to application-based services, such as Jakarta's use of online transportation apps. Users, particularly those from generation Z (persons born between 1995 and 2009). This generation is noted for being closely associated with the usage of information and communication technology, as well as a preference for fast-paced activities (spontaneous). Given the current situation, the purpose of this study is to determine and assess whether Generation Z online transportation users are content with switching to cashless payments in terms of switching intention, switching cost, and attitude toward price promotion. The findings of this study in Jakarta explain all accepted assumptions utilizing structural modeling with SMART PLS and 200 participants (online transportation service customers from generation Z). Switching costs have a big impact on switching intentions, according to this research. In addition, this research demonstrates that switching intention has a major impact on satisfaction. The study's third finding shows that one's attitude regarding price promotions has a considerable impact on switching intentions. Additionally, satisfaction is influenced by one's attitude toward price promotions. As a result, this research demonstrates that Attitude on Price Promotion (AOPP) can moderate the influence of switching costs on switching intention. The findings of this study suggest that internet transportation service providers should be able to sustain a price-related promotional approach. This is based on the findings of this study, which show that if users' attitudes are influenced by the presence or absence of price promotions, they will be easy to modify.